Penguatan Karakter Islami Dan Kreativitas Siswa Mi Ma’arif Bego Sleman Yogyakarta Melalui Kegiatan Mading Mingguan - Rofiqi, Mohammad; Ainur Rahmah, Halizah; Sultoni Adib, Muhammad; Amirah Maulida, Shofa; Haswina Riski Alaziz, Manda; Dicky Kurniawan, Muhammad (Al-ihsan: Jurnal Pengabdian Agama Islam, 2024)
Wall Magazine development activities are carried out so that students are able to improve their Islamic character through mading by getting used to honesty, responsibility, cooperation and discipline. This is reflected in the collaborative process of managing the wall magazine, starting from theme planning, collecting works, to publication. Apart from that, this activity is carried out to encourage students' creativity, especially in terms of writing, drawing and visual design skills. The method of making a wall magazine begins with information on the urgency of having a school wall magazine by the assistants, followed by the layout of each news item, and finalization. With these processes, MI Ma'arif Bego students can work together, respect and honor the opinions of others, and care about the work of others. Instilling Islamic values ​​into the content of the media is a key aspect that provides deep meaning for students, so that this activity not only builds technical skills, but also forms an Islamic personality. Methods of activities carried out include making wall boards in grades 4 and 5, providing media development so that students can easily work together in making wall plates. The creation of weekly wall magazines at MI Ma'arif Bego is a forum for instilling Islamic character values ​​to MI M'arif Bego students. Cooperation, mutual respect and appreciation, and caring about the work of others are parts that can be instilled. So is creativity, which has so far received less attention. The existence of weekly wall magazines is a demonstration of creativity in compiling and making wall magazines.